Bile Salt and Acid Tolerant of Lactic Acid Bacteria Isolated from Proventriculus of Broiler Chicken - E Damayanti; H Julendra; A Sofyan; SN Hayati (Media Peternakan, 2014)
The aim of this research was to obtain the lactic acid bacteria (LAB) as probiotic candidates which have resistance to bile salt and acid condition. LAB was obtained using isolation method from proventriculus of broiler chicken. Selective MRS media with 0.2% CaCO3 addition were used for LAB isolation using pour plate sampling method under anaerobic condition. The result showed that four selected isolates had morphological and biochemical characteristics as LAB. The selected LAB was characterized as follow: antibacterial activities, antibiotic sensitivity, resistance on bile salt, gastric juice and acid condition, and biochemical identification. Antibacterial activities assay of cell free supernatant was confirmed using disc paper diffusion method which was arranged on factorial design and each treatment consisted of three replications. The cell free supernatant of LAB isolates had antibacterial activities against Escherichia coli, Pseudomonas aerugenosa, and Salmonella pullorum. Molecular identification procedure using 16S rRNA sequence analysis showed that R01 and R02 as Pediococcus acidilactici. The viability of the two isolates were tested by acid pH (pH 1, 2, and 3), gastric juice pH 2, and bile salt condition for digestives tract simulation. The result showed that R01 and R02 had a high viability percentages at pH 1, 2, and 3 (95.45%, 99.49%, 104.01%, and 67.17%, 120.74%, 103.4%, respectively) and at bile salt simulation for 1-2 hours (100.35%-102.71% and 100.02%-102.65%, respectively), but at gastric juice simulation for 1-2 hours, the P. acidilactici R01 had higher viability than P. acidilactici R02 (59.69%-76.53% versus 43.57%-40.69%, respectively). In the antibiotic sensitivity test for three antibiotics (i.e. erythromicin 15 µg, penicillin G 10 µg, and streptomycin 10 µg), the P. acidilactici R02 showed resistance to Streptomycin and Penicillin. It is concluded that P. acidilactici R01 and P. acidilactici R02 isolated from proventriculus of broiler chicken potential as probiotic candidates for chicken.